Pengaruh Teknologi Terhadap Manajemen Dakwah - Ahmad Munawaru zaman (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2018)
Very large technological influence on da'wah management. As we all know, the advancement of information technology has a positive and negative impact. The positive impact of technological advancements is very useful and helps human life and activities. As for the negative impact when this technological progress is misused. With the progress of this technology, humans can quickly give and receive a good or bad thing and influence each other. In the development of da'wah, the influence of technology can be seen from the use of information technology as a medium of propaganda. The use of this technology can help make da'wah activities more effective and can reach wider propaganda goals. technological progress according to influencing human behavior as a target of da'wah. Changes in human behavior also bring about the dynamics and challenges of da'wah to be greater, so the management of da'wah must also develop. This paper attempts to explain the influence of information technology on the management of da'wah.